How does pension saving change when individuals complete repayment of their mortgage? - Rowena Crawford (Institute for Fiscal Studies (IFS), 2020)
We examine the extent to which owner-occupiers in their 50s and 60s change their private pension saving when they complete repayment of the mortgage on their primary residence. Using panel data from a household survey, the English Longitudinal Study of Ageing, we identify those who completed repayment of their mortgage as anticipated two years prior. Despite mortgage expenditures falling by over 200 per person on average, there is little resulting change in average pension saving. This is because only a small minority of individuals react - the probability of an individual increasing their monthly pension saving by more than 150 increases by only 5 percentage points on completing repayment of a mortgage. This suggests that if policymakers wish to influence behaviour in order to increase private pension saving, interventions targeted at those completing their mortgage repayment could be a tractable approach. Such individuals would be able to increase pension saving while maintaining spending at recent levels.
Keywords: D14; D15; 330; Altersvorsorge; Sparen; Hypothek; Rückzahlung; England